Hypoxia-inducible Factor-2α Probably Mediated the Toxicities of Intravenous Beta-Cyclodextrin in Normal and Diabetic Rats’ Kidneys - Anita Purnamayanti; Suharjono; Mahardian Rahmadi (Universitas Airlangga, 2025)
Background: Intravenous β-cyclodextrin administration poses an increased risk of toxicity. Objective: This study aimed to determine the nephrotoxicity of intravenous beta-cyclodextrin (BCD) and its underlying molecular mechanism. Methods: Sixteen Wistar rats were randomly assigned to the healthy or diabetic test group, which received a daily intravenous injection of water for injection or a 6% beta-cyclodextrin solution, respectively, for 28 days. Histopathology was analyzed semi-quantitatively on a 0-5 score basis, and RT-PCR was used to quantify the mRNA expression of HIF-1, HIF-2, IL-1, IL-6, IL-18, and eNOS. Results: There were no deaths in any of the groups, and renal function declined in the test groups. Histopathological findings revealed abnormalities in vascular integrity, cellular infiltration/damage, and necrosis in the kidney, while the relative expression of mRNA for hypoxia-inducible factors (HIFs), a marker of regional renal hypoxia, was upregulated. Conclusion: Intravenous administration of beta-cyclodextrin increases the risk of nephrotoxicity, and the molecular mechanisms underlying kidney injury are probably mediated by hypoxia inducible factors-2α (HIF-2α). We strongly suggest that future research should be conducted with an adequate sample size.